On Certain Subclass of Analytic Functions with Fixed Point. (14th February 2013) - Al-Hawary, T.; Frasin, B. A.; Darus, M.
Abstract : A new certain differential operator T α, β, δ, λ m f ( z ) and a subclass S m, w * ( α, β, γ, δ, λ ) are introduced for functions of the form f ( z ) = ( z − w ) − ∑ n = 2 ∞ a n ( z − w ) n which are univalent in the unit disc U = { z ∈ ℂ : | z | < 1 } . In this paper, we obtain coefficient inequalities, distortion theorem, closure theorems, and class preserving integral operators of functions belonging to the class S m, w * ( α, β, γ, δ, λ ) .